The Brazilian rural development model in the context of green economy - Lauro Mattei (International Labour Organization (ILO), 2015)
This paper discusses the Brazilian rural development model in the context of Green Economy and the debate about sustainable development, issues that have been discussed in international sphere. In this way, conceptions and new concepts have been defined which clarify the ideas and mechanisms involved in this new approach. In general terms, these conceptions and concepts have proposed the organization of another social order that looks beyond purely economic aspects. These themes were the starting point for the Rio +20 Conference in 2012. With these scenarios in mind, this paper will try to answer the following question: Is the green economy approach a good way to promote sustainable development in countries like Brazil? To answer this question we are concentrating our analysis in the agricultural sector. After a briefly discussion about the ideology and the thesis contemplated in the expression, "green economy" and the current development model in Brazil, we analyzed the Brazilian rural development model and the public investment in the agricultural and livestock sector, seeking to emphasize the government option towards primary commodity production for international markets. The main conclusions of the paper is that to understand the Brazilian society today we need to take in account the transition from an agrarian society to an industrial society, a process that occurred in Brazil during the 20th Century. This path Brazilian society has mapped since its inception is marked by the contradiction between abundance for a few portions of the population and famine for the great majority. It is important to register that this contradiction was enhanced during the post-war period and led Brazil to figure among the most contradictory countries in the world: if the year 2011 showed Brazil to be the 6th largest economy in the world, at the same time it continued to be the country with the greatest inequalities in the world and the greatest rates of social exclusion. So, we can conclude that these are exactly the social and political problems that continue to impede a more just and equal Brazilian society from taking shape, both in its rural and urban environments.
Keywords: 330; rural development; agricultural development; sustainable development; environmental protection; Brazil